Produção de sequências com base na análise experimental de relações ordinais em pré-escolares - MICCIONE, Mariana Morais (Universidade Federal do Pará, 2020)
The paradigm of ordinal relations provides interpretation tools that support the analysis of acquisition of ordinal academics behavior involved in math literacy. Studies investigated the effect of conditional in the visual modality on the production of sequences using the overlapping procedure. The use of conditional stimuli in the auditory modality and in combination with this procedure appears as a variable to be investigated. The general objective of this research was to investigate the production of sequences based on experimental analysis of ordinal relations in preschool children without cognitive limitations through training overlapping 2-stimulus sequences. The sessions occurred in two rooms of a Municipal Center for Early Childhood Education. The computerized program PROLER (versions 6.3 and 6.4) was used for stimulus presentation on the computer screen and for recording the response of point to stimuli by the participants. Two studies were formed by three experiments each one. The first experiment examined the formation of ordinal relationship after teaching of two sequences (numerals 1 to 6 and their quantities). Experiment 2 examined the emergence of these ordinal relations under conditional control in the auditory modality. Experiment 3 aimed to investigate the extension of conditional control in auditory modality to six new numerosity stimuli over ordinal relations. In Study 1: a) all five participants had scores above the chance level on transitivity tests and mastered less than 50% of substitution test trials in Experiment 1; b) two out of the three participants responded partly and presented more than 50% accuracy in transitivity tests and there was no formation of ordinal classes by any participant in Experiment 2; c) of three participants, one achieved 100% accuracy in the pretest to Experiment 3 and two responded partially to functional reversal and transitivity tests. Study 2: a) all had scores above the chance level on transitivity and substitute tests in Experiment 1, b) all participants showed more than 50% accuracy in transitivity tests and there was no formation of ordinal classes in Experiment 2; c) all participants achieved 100% accuracy in the pretest to Experiment 3. The results were discussed in terms of better understanding of ordinal response variables under conditional control in auditory modality in preschoolers. Results prove the extension of conditional control in auditory-visual modality and ensure the principle that the effects of a variable applied to stimulus of a class extends to other members of the same class.